Pengembangan Industri Kecil dan Rumah Tangga Alas Kaki dalam Menuju Keberlanjutan Usaha dan Menghadapi China-ASEAN Free Trade Agreement - Ma'mun Sarma; Farida Ratna Dewi; Edward H Siregar (Institut Pertanian Bogor, 2014)
Although the footwear industry is one sector of the small and medium industries which supported by the government, but the development of the industry is still relatively low. Various government policies have been made related to export and import settings, however the policies do not seem to provide significant benefits to the national development of the footwear industry. The condition is further exacerbated by the implementation of CAFTA (China-ASEAN Free Trade Agreement) in Indonesia. The lack of preparedness of local industry in the face of Chinese products in the country is feared to suppress the competitiveness of local products become increasingly weak. Therefore, the main objective of this study is to analyze the factors that influence the development efforts of small and household footwear industries and to analyze the effect of CAFTA on the sustainability of small and household footwear industries. The research was conducted in Bogor (district and city) which is a center of footwear industry in Indonesia. The respondent of the study consists of the leading small and household industries taken by purposive sampling with 100 respondents. Data were analyzed using the statistical descripitive and Structural Equation Modeling (SEM). Based on SEM analysis, the results indicate that efforts to develop small and household footwear industries directly affected by motivation efforts of the entrepreneurs in this industry and the government policies that facilitate the entrepreneurs in this industry. Increasing the development of business sustainability is also directly influenced by the characteristics of the entrepreneurs who are able to optimize productivity and the CAFTA implementation which is responded by good competitiveness from the local industry.